Enhancing Organizational Performance through Agile Coach‎ing: The Role of Organizational AgilityNeurological Dominance, Spiritualityand Culture - Risal, Taufiq; Lie, Darwin; Lubis, Fajar Rezeki Ananda (International Journal of Accounting and Economics Studies, 2026)
This study examines the impact of Agile Coaching on Organizational Agility and Organizational Performance, with particular attention to ‎the moderating roles of Neurological Dominance, Spirituality in the Workplace, and Organizational Culture. Using a quantitative research ‎design, the study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the direct relationships among the constructs and the moderating effects within the proposed model. Data were collected from 160 volunteers and employees of the Halaqah Silsilah Ilmiah (HSI) Foundation in Indonesia who participated in the Agile Hijrah Coaching program conducted in collaboration with the International Open University. The findings indicate that Agile Coaching significantly enhances both Organizational Agility and Organizational ‎Performance. Organizational Agility also shows a significant positive association with Organizational Performance. Moreover, Neurological ‎Dominance and Spirituality significantly moderate the effects of Agile Coaching on agility and performance, thereby strengthening coaching ‎effectiveness. In contrast, Organizational Culture does not exhibit a significant moderating effect. Although the study is limited to a single ‎organizational context, the results offer important implications for both theory and practice. Organizations are encouraged to implement agile ‎coaching initiatives with greater awareness of cognitive and spiritual diversity to improve adaptability and performance, while aligning cultural values more deliberately with agile principles. This study contributes to the literature by highlighting the roles of cognitive and spiritual ‎factors as key contextual moderators in agile coaching, providing a comprehensive perspective on agile transformation in dynamic organizational environments.
Keywords: Agile Coaching; Organizational Agility; Organizational Performance; Neurological Dominance; Workplace Spirituality; Organizational Culture.